Extracellular matrix deposition precedes muscle-tendon integration during murine forelimb morphogenesis - Yue Leng; Sarah N. Lipp; Ye Bu; Hannah Larson; Kathryn R. Jacobson; Haley A. Colling; Sarah Calve (Communications Biology)
Abstract The development of a functional musculoskeletal system requires the combination of contractile muscle and extracellular matrix (ECM)-rich tendons that transmit muscle-generated force to bone. Despite the different embryologic origins, muscle and tendon integrate at the myotendinous junction (MTJ) to connect across this interface. While the cell-cell signaling factors have received considerable attention, how the ECM links these tissues remains unclear. Here, we show the 3D distribution of ECM during forelimb development in wildtype (WT) and muscle-less Pax3 Cre/Cre mice. At E12, prior to MTJ integration, an aligned ECM is present at the presumptive insertion of the long triceps into the ulna. Tendon-like and muscle compartmentalization structures still form when muscle is knocked out; however, MTJ-specific ECM is not observed when muscle is absent. Our results show that the architecture of the muscle-tendon unit is established independent of muscle, but muscle is needed for the proper assembly of ECM at the MTJ.